2021
DOI: 10.1021/acs.inorgchem.1c02325
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Synthesis and Dielectric Properties of LaTaON2

Abstract: The development of new synthetic methodologies of perovskite oxynitrides is challenging but necessary for the search of new compounds and the investigation of new properties. Here, we report a new method of preparation of the perovskite LaTaON 2 that has been investigated as a pigment and photocatalyst for water splitting. The synthesis proceeds through the solid-state reactions under N 2 at 1500 °C between La 2 O 3 , LaN, and Ta 3 N 5 or between LaN and TaON, which are completed after 3 h and lead to sintered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…Considering the charge compensation, this stoichiometry is consistent with the presence of reduced Ta and Eu cations with the formal plausible composition Eu 2+ (Ta 0.37 4+ Ta 0.63 5+ )­O 2.37 N 0.63 . The existence of 100% of europium in the divalent state agrees with the observed effective magnetic moment of this compound (see below), whereas the +4 oxidation state of tantalum has been suggested in other perovskite oxynitrides coexisting with the more stable Ta 5+ cation. The electron diffraction patterns of EuTaO 2.37 N 0.63 indicated a cubic perovskite cell of a ≃ 4.0 Å with the space group of aristotype Pm 3̅ m (Figure ). This result differs from our previously reported electron diffraction study of EuTaO 2 N prepared by ammonolysis, which showed additional reflections indicative of a tilted I2 / m superstructure with a , b = √2 a 0 and c = 2 a 0 . , The perovskite Eu 3 Ta 3 O 3.66 N 5.34 (phase II) was prepared with reaction 2 at the same temperature than EuTaO 2.37 N 0.63 , under N 2 with y = 1.8 (initial ratio N/O of 3.78).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Considering the charge compensation, this stoichiometry is consistent with the presence of reduced Ta and Eu cations with the formal plausible composition Eu 2+ (Ta 0.37 4+ Ta 0.63 5+ )­O 2.37 N 0.63 . The existence of 100% of europium in the divalent state agrees with the observed effective magnetic moment of this compound (see below), whereas the +4 oxidation state of tantalum has been suggested in other perovskite oxynitrides coexisting with the more stable Ta 5+ cation. The electron diffraction patterns of EuTaO 2.37 N 0.63 indicated a cubic perovskite cell of a ≃ 4.0 Å with the space group of aristotype Pm 3̅ m (Figure ). This result differs from our previously reported electron diffraction study of EuTaO 2 N prepared by ammonolysis, which showed additional reflections indicative of a tilted I2 / m superstructure with a , b = √2 a 0 and c = 2 a 0 . , The perovskite Eu 3 Ta 3 O 3.66 N 5.34 (phase II) was prepared with reaction 2 at the same temperature than EuTaO 2.37 N 0.63 , under N 2 with y = 1.8 (initial ratio N/O of 3.78).…”
Section: Resultssupporting
confidence: 75%
“…The reaction used, the proportions of the reactants, the selected gas, and the maximum synthesis temperature determined the average nitrogen content of the sample per Eu or Ta mol, which was tuned from x = 0.63 to 1.78, and the phase composition. We have recently reported a similar synthetic approach for the preparation of LaTaON 2 and slightly nitrogen-deficient LaTaO 1.12 N 1.88 that we investigated for their dielectric properties . Both compounds were prepared either from LaN and TaON or from La 2 O 3 , LaN, and Ta 3 N 5 at 1500 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, these contents were below the nitrogen stoichiometry in the mixture of reactants (3, 3.25, 3.56, and 1.96 for La, Ce, Nd, and Eu samples, respectively), indicating the incorporation of extra oxygen in the samples during synthesis. Nitrogen loss at high temperatures has been observed in other tantalum perovskites such as SrTaO 2 N and LaTaON 2 and has been interpreted as a decomposition reaction releasing N 2 with partial reduction of Ta 5+ to Ta 4+ , analogous to the oxygen loss of transition metal oxides at high temperatures that produces reduced oxides together with O 2 . The corresponding cation ratios determined by EDX were La/Ta = 1.82(17), Ce/Ta = 1.81(10), Nd/Ta = 1.77(17), and Eu/Ta = 1.89(15), which agree with the nominal compositions within the experimental error.…”
Section: Resultsmentioning
confidence: 98%
“…EuTaO 2 N, EuNbO 2 N, and EuWO 1+ x N 2– x are ferromagnetic with T c values between 5 and 12 K because of Eu 2+ spin ordering. LaTiO 2 N and RHfO 2 N (R = La, Nd, Sm) compounds are visible light-active photocatalysts in water oxidation and reduction, whereas LaTaON 2 , in addition to a photocatalyst for water splitting, is a high-dielectric permittivity material …”
Section: Introductionmentioning
confidence: 99%